2022
DOI: 10.3390/life12111765
|View full text |Cite
|
Sign up to set email alerts
|

Active Biomolecules from Vegetable Extracts with Antitumoral Activity against Pancreas Cancer: A Systematic Review (2011–2021)

Abstract: The emergence of resistance to pancreatic cancer (PC) current treatment requires the development of new therapeutic strategies. In this context, bioactive molecules from plant extracts have shown excellent properties to improve classical therapy against this type of tumor. This systematic review aims to collect all the in vitro studies related to the antiproliferative activity of isolated plant molecules that support their applicability in PC. A total of 620 articles published in the last 10 years were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…In the specific case of apoptosis, it was observed that methanol is the most commonly used solvent, and its extracts have apoptotic potential against the RH-30 and RD cell lines [21,23]. On the contrary, it should be noted that, in the scientific literature on extraction methods for bioactive compounds of plant origin, ethanol is the most commonly used for the extraction of polyphenols [60]. However, for RMS cells, most of the extracts were obtained with methanol, showing high amounts of polyphenols and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific case of apoptosis, it was observed that methanol is the most commonly used solvent, and its extracts have apoptotic potential against the RH-30 and RD cell lines [21,23]. On the contrary, it should be noted that, in the scientific literature on extraction methods for bioactive compounds of plant origin, ethanol is the most commonly used for the extraction of polyphenols [60]. However, for RMS cells, most of the extracts were obtained with methanol, showing high amounts of polyphenols and flavonoids.…”
Section: Discussionmentioning
confidence: 99%